Heavy metals accumulation on black tilapia sp. exposed to municipal solid waste landfill leachate and the health risk assessment - Abdul Rahman, Umi Raihana (2016)
Uncontrolled production and discharge of untreated landfill leachate poses environmental pollution. The hazardous contaminants such as heavy metals is pass through food chain via fish bioaccumulation and end up in human bodies. Tilapia is a type of fish that can adapt to a wide range of pollutants in various water conditions and are resistant to disease. Tilapia has high market demand for its edible nature and it is also vulnerable to leachate contamination in Malaysia. Objective: To assess level of heavy metals accumulation in Tilapia sp. exposed to municipal solid waste landfill leachate which were young and old leachate and the health risk associated via Tilapia consumption. Methodology: Landfill leachate from a young and old landfill were tested for physicochemical characteristic and heavy metals (copper, cadmium, lead, nickel, arsenic). Young leachate is leachate from a young landfill with less than five years old whereas old leachate is leachate from an old landfill, a landfill with more than 10 years of age. Ten Tilapia fish were exposed to leachate at different concentrations (2% to 20% v/v) for 96 hours to measure the level of heavy metal accumulations in the fish muscle and gills. Fish samples were digested using acid digestion method and heavy metals were determined using ICP-OES. Bio-concentration factor (BCF) of heavy metals in the fish muscle and gills were calculated. Health Risk Assessment was calculated to determine the safety for human consumption through Hazard Quotient (HQ), Hazard Index (HI) and Lifetime Cancer Risk (LCR). Results: Fish exposure to old leachate produces high heavy metal accumulations rate in fish compared to the young leachate. Cu, Pb and Ni were highly accumulated in the gills compared to the muscle. The highest Cu was detected in the fish gills at 6% v/v leachate concentration (22.72 ± 0.60 mg/kg) followed by fish muscle at 8% v/v leachate concentration (18.30 ± 0.36 mg/kg) in fish exposed to old leachate. The highest Ni was detected in the fish gills at 8% v/v leachate concentration (1.66 ± 0.021 mg/kg) and 4% v/v leachate concentration (1.34 ± 0.033 mg/kg) compared to fish muscle at 8% v/v leachate concentration (1.32 ± 0.024 mg/kg) in fish exposed to old leachate. Pb was the highest at 8% v/v of old leachate in fish gills (0.50 ± 0.011 mg/kg). Cd was commonly detected in fish gills and muscle with the highest concentration detected at 8% v/v leachate concentration (0.14 ± 0.01 mg/kg). High heavy metals accumulation on fish occur at 6% and 8% v/v of leachate concentration. The highest BCF was determined for Cu in gills with the value of 2186.67 at 2% v/v and 4544 at 6% v/v of old leachate. There was a non-carcinogenic risk of the exposure to combination of metals (Cu, Cd, Pb and Ni) due to fish consumption in fish expose to young and old leachate (HI > 1) and carcinogenic health risk of the exposure to Cd (LCR > 1 x 10-4) via Tilapia consumption. Conclusion: The accumulation rate of heavy metals were higher in fish gills exposed to old leachate. There is a possibility of health risk from heavy metals exposure of municipal waste landfill leachate via fish consumption.